2010
DOI: 10.1165/rcmb.2009-0073oc
|View full text |Cite
|
Sign up to set email alerts
|

Actin Cytoskeleton Regulates Stretch-Activated Ca2+ Influx in Human Pulmonary Microvascular Endothelial Cells

Abstract: During high tidal volume mechanical ventilation in patients with acute lung injury (ALI)/acute respiratory distress syndrome (ARDS), regions of the lung are exposed to excessive stretch, causing inflammatory responses and further lung damage. In this study, the effects of mechanical stretch on intracellular Ca 21 concentration ([Ca 21 ] i ), which regulates a variety of endothelial properties, were investigated in human pulmonary microvascular endothelial cells (HPMVECs). HPMVECs grown on fibronectin-coated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 57 publications
3
45
0
Order By: Relevance
“…The ϽEϾ(␦) results for untreated BLMVECs did not display a sigmoidal shape, so the fitted results were inconclusive. The biomechanical role of cellular structures below the glycocalyx was investigated by treating the cells with cytochalasin D. Cytochalasin D is known to inhibit actin polymerization within the cell, thus causing softening of the cell (18). tions (100 Ͻ ␦ Ͻ 500 nm), for control and enzyme-treated BLMVECs (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The ϽEϾ(␦) results for untreated BLMVECs did not display a sigmoidal shape, so the fitted results were inconclusive. The biomechanical role of cellular structures below the glycocalyx was investigated by treating the cells with cytochalasin D. Cytochalasin D is known to inhibit actin polymerization within the cell, thus causing softening of the cell (18). tions (100 Ͻ ␦ Ͻ 500 nm), for control and enzyme-treated BLMVECs (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…However, in terms of expression of structural genes such as TnnT1, a marker for muscle contractility, another potential regulatory mechanism might be strain-induced opening of Ca 2+ channels. It has previously been reported that mechanical stimulation increases intracellular Ca 2+ concentrations in human lung fibroblasts [83], human pulmonary microvascular endothelial cells [84] and neonatal rat myocytes [85] in a transient manner. The transient increase in intracellular Ca 2+ levels shows a similar pattern as observed by Takayama et al after electrical stimulation of C2C12-derived myotubes.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, many ion channels localize to caveolae and several cardiac arrhythmias are related to caveolae malfunction (Balijepalli and Kamp, 2008). Interestingly, stretch-activated Ca 2+ influx through stretch-activated ion channels, some of which are localized in caveolae and/or regulated by caveolins (Gervasio et al, 2008), depends on an intact actin cytoskeleton, which raises the possibility that the association of caveolae with stress fibers might fine-tune these membrane channels (Hayakawa et al, 2008;Ito et al, 2010). A specific role for caveolae, mediated by their ability to flatten out, has recently been demonstrated in the regulation of osmotic swelling activated chloride channel I Cl,swell .…”
Section: Caveolae Regulate Other Mechanotransduction Pathwaysmentioning
confidence: 99%